Pengaruh Bauran Pemasaran Terhadap Minat Beli Melalui Sikap pada Anggota Potensial Community Supported Agriculture Seni Tani, Kota Bandung - Maharani, Nindya Kintan; Sadeli, Agriani Hermita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Seni Tani is the first urban agriculture social enterprise in Bandung City that adopts the Community Supported Agriculture (CSA) system, connecting consumers with farmers directly. Although there is an increasing trend in the amount of vegetable consumption in Bandung City in 2019-2023, the number of consumers who subscribe to the Seni Tani CSA program is still relatively low. However, when viewed from the number of Seni Tani Instagram followers, it is very high to become a potential members of CSA Seni Tani. This study aims to analyze the influence of 7P’s marketing mix on purchase intention through attitudes in potential members of CSA Seni Tani. This research used a quantitative research design with a questionnaire survey approach. This study used a sample of 100 people obtained through convenience sampling. The data analysis technique used in this study is a path analysis test using the SPSS version 25 program. The results of this study indicate that the marketing mix strategy is proven to have a positive and significant influence on purchase intention through attitudes of potential members. Attitude has a positive and significant direct influence on purchase intention, while the marketing mix does not have a direct influence on purchase intention, but through the mediating variable in the form of attitude.